Validation of Instruments for Systems Thinking and Complex Problem-Solving Skills on Environmental Pollution Using the Rasch Model Approach - Ade Supriatno; Ida Kaniawati; Irma Rahma Suwarma (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to test the validity and reliability of the System Thinking (ST) and Complex Problem Solving (CPS) instruments developed for vocational high school students. A quantitative approach was used using the Rasch model with the Winsteps tool. The ST instrument consisted of 8 multiple-choice items analyzed with a dichotomous model, while the CPS instrument consisted of 9 essay items with a polytomous model, and was tested on 11th-grade vocational high school students who had already learned about environmental pollution, with a total of 36 respondents. The analysis included unidimensionality, item fit, item–total correlation, reliability, and Wright Map mapping. The results showed a Raw Variance Explained by Measures of 41.3% (ST) and 44.3% (CPS), indicating that unidimensionality was fulfilled. The MNSQ Infit–Outfit values were within the ideal range of 0.5–1.5, with Point Measure Correlations of 0.37–0.85 (ST) and 0.46–0.75 (CPS). Person reliability was 0.87 (ST) and 0.75 (CPS), respectively, while item reliability was 0.92 (ST) and 0.86 (CPS), indicating high measurement consistency. The logit range on the Wright Map showed a balance between student ability and item difficulty. Thus, the ST and CPS instruments are proven to be valid and reliable for comprehensively measuring System Thinking and complex problem-solving abilities.